PEMODELAN INFRASTRUKTUR MENGGUNAKAN FRAMEWORK OIAM (STUDI KASUS PS. AS PUTRA) - Aji Permana (NUANSA INFORMATIKA, 2015)
PS. AS PUTRA is a company engaged in chickens and feed distributors. PS. AS PUTRA a company which has been implementing ICT in business processes but existing infrastructure is still not good. Therefore, it needs a special model of defining the infrastructure, so that the existing infrastructure can be targeted in order to obtain a description of the infrastructure required for the development of infrastructure and enterprise systems PS. AS PUTRA. Open Infrastructure Architecture Model is a framework that is able to bring the company achieve the desired objectives with concrete measures to ensure the optimal use of architecture. OIAm able to define the "capability" or the ability of a solution to a set of quality attributes. OIAm bring business agility, effectiveness of landscape architecture and infrastructure are managed and expanded in the hand of any organization. The results obtained in this thesis report generates a Landscape Infrastructure on the need for infrastructure companies PS. AS PUTRA. Modeling infrastructure in the company PS. AS PUTRA use Framework OIAm the components used in the modeling covers Working Areas, Environment, Building Blocks, Elements and Quality attributes. Keywords: Infrastructure Landscape, Open Infrastructure Architecture Model, Agribusiness